Folkeoplysning og ungdomsliv - et indlæg ud fra Søren Ehlers, Ungdomsliv (2000) - Wåhlin, Vagn (Grundtvig-studier, 2003)
Folkeoplysning og ungdomsliv - et indlag ud fra Sorens Ehlers, ‘ Ungdomsliv ’ (2000)[‘ Folk’-Education and Youth: Reflections upon Soren Ehlers, ‘ Ungdomsliv ’ (2000)]By Vagn WahlinSøren Ehlers, Ungdomsliv. Studier i den folkeoplysende virksomhed for unge i Danmark 1900 -1925 [The Youthful Years: Studies in the ‘ Folk’- Education of the Young in Denmark 1900 - 1925] (Alinea, Copenhagen, 2000), 281 pp.In January 2000 there was considerable media discussion and an unusually vociferous gathering at Danmarks Padagogiske Universitet [The Danish University of Education] over university lecturer Soren Ehlers’ public defence of his thesis, where Ehlers convincingly demonstrates that the influence of Grundtvig and the Grundtvig legacy upon the education of Danish youth has been overrated seen in relation to the influence of relevant initiatives and trends at home and abroad. The book also offers an introduction to new approaches in educational research.This article critically addresses some major points arising from the study. In general, Ehlers’ readable presentation of an impressive quantity of comprehensive material and data deserves praise: firstly, as a solid introduction to and outline of a complicated educational debate and secondly, as a much needed platform for further investigations in the matter of upbringing, educating and morally influencing young people.Regrettably, the author’s approach is by the uncritical introduction of ill-fitting theory (I) from UNESCO’s concepts and categorisations (formal/non-formal/informal) of educational patterns; (II) from relatively recent Danish ethnological-anthropological theory about three dominant life-forms, namely (a) the self-employed - such as farmers, shop-keepers and minor craftsmen; (b) the wage-earning - such as industrial workers, unskilled workers and lower functionaries; and (c) the vocational – such as teachers, clergy, businessmen; and (III) from relatively recent Danish political science which divides society into four chief sectors, namely (a) the public - covering state, municipal and political organisations; (b) the private - profit-dominated businesses, factories and co-operatives; (c) the voluntary - non-profit-making organisations such as local sports associations, charities and Christian associations; and (d) the family and other social and local networks.All theories, I-III, are used in a pell-mell manner, with a stiff logic unconstrained by proper qualifications; and thus they weaken rather than illumine the study. What is worse: although, as Ehlers rightly argues, there is indeed need of a higher level of theoretically based research in the humanities and religious studies, it is to be feared that this book will rather scare researchers away than convince them to cultivate that theoretically-based approach.